Developing the next generation of dissemination and implementation researchers: insights from initial trainees - Stamatakis, Katherine A (BioMed Central, 2013)
BACKGROUND: Dissemination and implementation (D&I) research is a relatively young discipline, underscoring the importance of training and career development in building and sustaining the field. As such, D&I research faces several challenges in designing formal training programs and guidance for career development. A cohort of early-stage investigators (ESI) recently involved in an implementation research training program provided a resource for formative data in identifying needs and solutions around career development. RESULTS: Responses outlined fellows’ perspectives on the perceived usefulness and importance of, as well as barriers to, developing practice linkages, acquiring additional methods training, academic advancement, and identifying institutional supports. Mentorship was a cross-cutting issue and was further discussed in terms of ways it could foster career advancement in the context of D&I research. CONCLUSIONS: Advancing an emerging field while simultaneously developing an academic career offers a unique challenge to ESIs in D&I research. This article summarizes findings from the formative data that outlines some directions for ESIs and provides linkages to the literature and other resources on key points.